Pengaruh Pemberian Makanan Buatan dengan Prosentase yang Berbeda Terhadap Pertumbuhan Ikan Bawal Air Tawar (Colossoma macropomum) yang Dipelihara dalam Karamba di Sungai - Mardani Mardani (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
This experiment provide information about artificial feed, which is needed for the growth of fishes. The goal is to determine the effect of feeding with different percentage of artificial feed on the growth of Tambaqui (Colossoma macropomum) which were reared in cages in river. The best results in this experiment is feeding 7% of artificial feed containing 30% protein, 8.1% fat, 14% carbohydrate, and DE 2.55 kcal.g-1.